The Effect of Different Temperatures and Moisture During Storage on Germination Indices of Flax Seed Oil (Linum usitatissimum L.) - S. Baladi; H.R. Balouchi; A. Moradi; M. Movahhedi Dehnavi (علوم و فناوری بذر ایران)
Storage conditions, especially high moisture storage and high temperature environments, greatly affect the quality of oil seeds. In order to investigate the effect of temperature, seed moisture content and storage time on the deterioration of flax seed oil a factorial experiment was conducted based on a completely randomized design with four replications in the seed lab of Yasouj University. The factors included the temperature at four levels (15, 25, 35 and 45 °C), moisture content in 5 levels (initial moisture content, 5, 9, 13 and 17%) and six storage times (30, 60, 90, 120, 150 and 180 days). The results showed that germination and  normal seedlings percentage, germination rate and vigor index reduced with increasing moisture content and during storage at each temperature level and with a combination of high temperature and moisture content this reduction was more severe. The lowest level of deterioration was in 5 °C with 5% moisture content that after 180 days storage, viability was reduced from 93 to 90 percent. Over time and with increasing moisture content, electrical conductivity also increased, and this increase was greater at high temperatures and seed lots with high electrical conductivity had low viability